2022
DOI: 10.1039/d2cp03485a
|View full text |Cite
|
Sign up to set email alerts
|

The evolution towards cyclic structures in the aggregation of aromatic alcohols: the dimer, trimer and tetramer of 2-phenylethanol

Abstract: Gas-phase spectroscopic studies of alcohol clusters offer accurate information on the influence of non-covalent interactions on molecular recognition, and are of paramount importance to model supramolecular and biological chemical processes....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…This work has shown that CREST, a recently introduced tool for isomer searches in computational chemistry, successfully identifies low energy isomers of chiral tag complexes. This work supports the emerging consensus from the rotational spectroscopy community that CREST is a highly successful method for identifying the low‐energy isomers of weakly bound complexes 50,51,77–93 . Further, geometry optimization using dispersion corrected DFT gives chiral tag complex equilibrium geometries with sufficient accuracy to make a high‐confidence determination of the analyte absolute configuration.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This work has shown that CREST, a recently introduced tool for isomer searches in computational chemistry, successfully identifies low energy isomers of chiral tag complexes. This work supports the emerging consensus from the rotational spectroscopy community that CREST is a highly successful method for identifying the low‐energy isomers of weakly bound complexes 50,51,77–93 . Further, geometry optimization using dispersion corrected DFT gives chiral tag complex equilibrium geometries with sufficient accuracy to make a high‐confidence determination of the analyte absolute configuration.…”
Section: Discussionsupporting
confidence: 72%
“…This work supports the emerging consensus from the rotational spectroscopy community that CREST is a highly successful method for identifying the low-energy isomers of weakly bound complexes. 50,51,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] Further, geometry optimization using dispersion corrected DFT gives chiral tag complex equilibrium geometries with sufficient accuracy to make a high-confidence determination of the analyte absolute configuration.…”
Section: Discussionmentioning
confidence: 99%
“…This energetic distribution is probably associated to the prevailing role in these complexes of the π ring electronic density and the large and polarizable molecular orbital distribution in the sulfur triatomics. In this sense both the S⋯π and S–H⋯π interactions occupy an intermediate position between the dominant dispersive character observed in π-stacking 26,27,55 and dimers involving a primary hydrogen bond, particularly alcohols, 56–58 but also some thiols like the prototypic hydrogen sulfide dimer. 59 On the other hand, the dimer of benzyl mercaptan, 60 which combines S–H⋯S and S–H⋯π interactions, presents an energy distribution close to the benzofuran dimers.…”
Section: Resultsmentioning
confidence: 98%
“…Similarly to 2-phenylethanol, [7][8][9][10][11][12][13] the potential energy surface of PET is described with three torsion dihedrals associated to the terminal side chain. Density functional and ab initio calculations predicted five stable structures within 8 kJ mol À 1 , shown in Figure 1.…”
Section: Potential Energy Surfacementioning
confidence: 99%
“…In 2‐phenylethanol the skew global minimum (Ggπ) benefits from a O−H⋅⋅⋅π intramolecular hydrogen bond to the ring, but five other conformations are also available below 8 kJ mol −1 . The structural preferences of the alcohol have been confirmed using mass‐resolved resonance‐enhanced multiphoton ionization (R2PI), [7] double‐resonance IR/UV ion‐dip, [8–10] ionization‐loss stimulated Raman [11] and microwave spectroscopy, [12,13] which detected the global minimum and a second plane‐symmetric isomer (At). Since the larger size and polarizability of sulfur is expected to decrease or modulate the hydrogen bonding capabilities of PET, [14,15] it is interesting to check which changes are introduced in the conformational landscape by the replacement of the oxygen atom by sulfur and whether a S−H⋅⋅⋅π weak hydrogen bond prevails in the bare molecule.…”
Section: Introductionmentioning
confidence: 98%